Evolution of Nepal’s National Security Council and National Security Policy - Sharma, Rajendra (Unity Journal, 2023)
In a democratic system, there is a discussion about who will be the "guardian of the guards." For this, the military is made answerable to the parliament and parliamentary oversight bodies are established to make military affairs transparent and accountable to the civilian government. Democratic countries have adopted security policies in which the civilian government controls security strategy and priorities, which were previously handled by the military. A high-level body has been established in various countries to provide strategic direction to the country. For example, the National Security Act of 1947 established the National Security Council (NSC) in the United States; the United Kingdom established one in 2010; and India and Nepal both established one in the post-1990. In Nepal, the NSC of 1990, with only two members and the Prime Minister as chairperson, was unable to bring civilians and military personnel together, resulting in a security dilemma. However, Constitution of Nepal (2015) explicitly enjoins the NSC to formulate security policy and other strategic policies. The Nepali security policy, namely the National Security Policy (NSP), was enacted for the first time in 2016 by the government. This NSP was said to be revised by th e government in 2019, but what about the policy and what were the NSC’s roles in policy formulation are still kept secret to date?In this backdrop, this paper focuses on whether and to what extent the government takes geopolitics and security sensitivities of Nepal into account while formulating the NSP and constituting the NSC. This will focus on raising the government's security priority and will aid in identifying the factors influencing the evolution of the NSC and NSP. Hence, the research question addressing this objective is mainly, "What are the factors contributing to the evolution and development of NSC and NSP in Nepal?" For this, the academic literature, domestic laws, and national security and defense policy were studied. In addition, semi-structured questionnaires were used to interview experts on national security in an attempt to explore the evolution of NSC and NSP in general and the practicality of security governance in particular. This paper concludes by defending the necessity of the NSP and NSC in articulating the security vision and maintaining some continuity in the future security vision of Nepal's decision-makers.